Working Capital Management and Sustainable Growth: the Mediating Role of Financial Performance - Muljono, Hari Tohar (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This paper purpose to test the effect of working capital management on Sustainable Growth and the indirect effect of financial Performance on Sustainable Growth. The model is advanced and tested using partial least-squares path modelling and data were collected from a sample of 156 manufacturing companies listed on the IDX during the period 2018 -2022. The finding demonstrate that working capital significantly affects financial Performance. Furthermore, working capital management exhibit a significant direct influence on sustainable growth and a significant indirect influence through financial Performance. Thus, this study suggests that firms need to manage their working capital to increase their profits and eventually to achieve sustainable growth. This research was only conducted on manufacturing companies listed on the Indonesian stock exchange which would limit the generalizability of the findings. This study supports the idea that companies can promote sustainable corporate growth through good working capital management. The study fills the lack of research on the relationship between Working Capital Management and Sustainable Growth mediated by financial performance.